The Power of Mind Mapping to Produce Good Writing Product - Abdul Aziz Rifa’at; Heru Setiawan (Institut Agama Islam Negeri Palopo, 2019)
The objective of this study was to find out the significant difference in writing achievement between the 11th grade students SMA Al-Amalul Khair Palembang who were taught by Mind Mapping technique and in that of those who were not. The second objective was to find out the improvement of the 11th grade students’ writing score at SMA Al-Amalul Khair Palembang after they were taught using Mind Mapping technique. The Quasi-experimental method through pretest-posttest non-equivalent control group design was used in this study. The population was all of 11th grade natural science students at SMA Al-Amalul Khair Palembang in academic year 2018/2019. The total number of the population was 52 students in which they were divided into two classes as class 11.1 and 11.2. The sample was taken non-randomly. Class 11.1 was chosen as the experimental group and class 11.2 was chosen as the control group. The total number of the sample in the experimental group was 22 students. The test was administered twice as pretest and posttest. The results of the tests were analyzed by using paired sample t-test and independent sample t-test through SPSS (Statistical Package for Social Sciences) program.